Acculturation and Physical Activity Among Latinas Enrolled in a 12-Month Walking Intervention. (July 2018) - Joseph, Rodney P.; Benitez, Tanya J.; Ainsworth, Barbara E.; Todd, Michael; Keller, Colleen
This report evaluates the relationship between acculturation and assimilation with the physical activity (PA) outcomes of a 12-month walking intervention for postpartum Latinas ( n = 81, M age = 29.2 years, M BMI [body mass index] = 30.0). PA was measured by ActiGraph GT1M accelerometers. Acculturation and assimilation were measured by the Hazuda Acculturation and Assimilation Scales. Data were collected at baseline, 6 months, and 12 months. Results showed a trend for participants classified in the least acculturated groups to engage in more moderate-to-vigorous PA than participants classified in the higher acculturated/assimilated groups for two dimensions of acculturation (Adult Proficiency in English Versus Spanish, p = .002; Adult Pattern of English Versus Spanish Language Usage, p = .001) and two dimensions of assimilation (Childhood Interaction With Members of Mainstream Society, p = .028; Adult Functional Integration With Mainstream Society, p ≤ .001). No other significant effects were observed. Findings highlight the continued need to understand the context in which acculturation and assimilation influence PA.